A thermospheric Na layer event observed up to 140 km over Syowa Station (69.0°S, 39.6°E) in Antarctica. Issue 10 (18th May 2015) - Tsuda, T. T.; Chu, X.; Nakamura, T.; Ejiri, M. K.; Kawahara, T. D.; Yukimatu, A. S.; Hosokawa, K.
Abstract We report a thermospheric Na layer event (up to 140 km) observed by lidar in the night of 23–24 September 2000 at Syowa (69.0°S, 39.6°E), Antarctica. The thermospheric Na number densities were 2–9 cm−3 at 110–140 km, 3 orders of magnitude smaller than the peak density of the normal layer at 80–110 km. The thermospheric Na layers exhibited a wave‐like structure with a period of 1–2 h. The colocated ionospheric/auroral observations showed sporadic E layers over Syowa through the night and an enhancement of the ionospheric/auroral activity around south side of Syowa at the event beginning. Adopting the theory by Chu et al. (2011), we hypothesize that the thermospheric Na layers are neutralized from converged Na+ layers. An envelope calculation shows good consistency with the observations.